ANALISIS VEGETASI DAN KEANEKARAGAMAN TUMBUHAN DI KAWASAN MANIFESTASI GEOTERMAL IE SUUM KECAMATAN MESJID RAYA KABUPATEN ACEH BESAR - Muslich Hidayat (Universitas Islam Negeri Ar-Raniry, 2017)
Ie Suum geothermal manifestation area is a hot sering resource in Ie Suum Village at Aceh Besar regency. Ie Suum hot spring is a stretch of Seulawah Agam mountain and is one of the most active volcanic mountains in Aceh. This area has higher temperature and soil pH compared to areas far from geothermal areas. Therefore, this study can be associated with the unique characteristics of vegetation of geothermal areas will be different from vegetation plants that exist in other vegetation types. This research was conducted by quadrat transect method by determining the location of the research by purposive sampling divided into four point (station) with size determined based on plant habitus that is: herb (1x1 m2), bush / shrub (2x2 m2), pole ( 5x5 m2), and trees (10x10 m2). Data analysis is done qualitatively and quantitatively. Quantitative analysis of data by using vegetation analysis are: density (Kr), Frequency (Fr), Dominance (Dr), and Diversity Index (Ä¤). The results of the study found 23 families consisting of 34 species with a total number of individuals as many as 534 scattered in 4 observation stations divided into herbaceous plants, shrubs, poles and trees. Important Value Index (INP) vegetation in geothermal manifestation area of Ie Suum in all stations was obtained by INP 225,86%. This value belongs to the high category. The species species that have the highest index of other species Axonopus compressus is 17.02%, while the lowest Importance Value Index is Clidemia hirta with a value of 1.32%. The high value of INP Axonopus compressus is due to this species living on dry soil moisture and high acidity. The biodiversity index (Ä¤) of geothermal area of Ies Suum of Mesjid Raya District of Aceh Besar is Ä¤ = 3,508. Vegetation of plants in the geothermal area ie suum belong to the high category due to plants that can adapt to high environmental physical-chemical conditions.